Characteristics and usefulness of trunk muscle endurance tests on the Roman chair in healthy adults - Petrič, Maja; Zaletel-Kragelj, Lijana; Vauhnik, Renata (PeerJ, 2022)
Background Adequate trunk muscle endurance is considered to be an important indicator of good low back stability; therefore, its assessment is needed when determining an individual’s risk for back pain. Optimal tests to assess each trunk muscle group separately are difficult to find. The objective of this study was to verify if two groups of trunk muscle endurance tests (standard and alternative) show comparable results in terms of muscle endurance ratios, holding times and rated perceived effort to perform each test. Methods The study was designed as a quasi-experimental repeated-measures design. There was a single group of participants who took part in two different trunk muscle endurance testing. Sixty-eight healthy adult volunteers, aged 20–45 years (31.9 ± 7.2 years), without recent musculoskeletal injury or disorder participated in the study. All participants finished the study. Trunk muscle endurance tests as tested on the Roman chair (B tests) were compared with standard tests as suggested by McGill (A tests). Each group of tests consisted of an endurance test for trunk extensors, trunk flexors, and lateral trunk muscles for left and right side. The order of tests’ performances was randomly assigned to each participant, whereby a participant did perform A and B tests in the same order. In each test of A and B the holding time was recorded and a perceived effort in each test performance was also assessed by participants. Post testing performance the four ratios of trunk muscles endurance comparison were calculated for each group of tests to determine if there is a good or poor ratio between muscles. Results of each participant were compared for trunk muscle endurance ratio calculations, holding times and rated perceived effort for A and B tests. Results Results showed comparable trunk muscle endurance ratios in the three ratios observed, except for the flexors:extensors ratio (AFL:EX: 1.2 (IQR: 0.7–1.6) vs. BFL:EX: 0.6 (IQR: 0.3–0.8); p < 0.001). As compared to A tests, holding times were significantly longer in B tests for the extensors (AEX: 125.5 s (IQR: 104.8–182.8 s) vs. BEX: 284.0 s (IQR: 213.0–342.3 s); p < 0.001) and lateral trunk muscles (AL-LM: 61.0 s (IQR: 48.3–80.8 s) vs. BL-LM: 131.5 s (IQR: 95.5–158.5 s); AR-LM: 63.5 s (IQR: 45.8–77.3 s) vs. BR-LM: 113.0 s (IQR: 86.3–148.8 s); p < 0.001), both were also rated as slightly easier to perform in the extensors (ARPE-EX: 13 (IQR: 12.0–14.0) vs BRPE-EX: 11 (IQR: 10.0–13.0); pRPE-EX < 0.001) and lateral muscles testing (ARPE-LM: 14.0 (IQR: 12.3–15.8) vs. BRPE-LM: 13.0 (IQR: 12.0–15.0); pRPE-LM = 0.001). Conclusions A and B tests are comparable in three of four trunk muscle endurance ratios, while longer holding times and lower perceived effort to perform were observed in most of the B tests. The Roman chair tests could be used as an alternative to standard tests.
Keywords: Trunk muscles; Endurance; Roman chair; Test characteristics